Internet boundaries for social networking: impact of trust and satisfaction - Norton, Aaron Michael (Kansas State University, 2011)
The present study examined whether married individuals hold boundaries for online social networking and the relationship between these boundaries and relational trust and satisfaction. Participants included 205 married individuals who had been married for an average of 27 years. Five specific boundaries were identified and tested using group comparison (by sex) structural equation modeling. Confirmatory factor analysis revealed two latent constructs for internet boundaries: Openness (3 items: Know Friends, Share Passwords and Account Access) and Fidelity (2 items: No Flirting and No Former Partners). Findings suggest that couples in long-term committed relationships have boundaries or rules for social networking. Furthermore, trusting one’s partner, but not relationship satisfaction, contributes to behaviors that reflect sharing online social networking information, and curb online flirting and relationships with former romantic partners. Trust was more strongly associated with men’s than women’s motivation to avoid flirtatious online interaction and communicating with former romantic partners online. These findings that indicate that the use of internet boundaries is highly related to marital trust support the development theory of trust.
Keywords: Marriage; Internet; Boundaries; Social networking; Computer mediated communication; Trust; Behavioral Sciences (0602); Communication (0459); Individual & Family Studies (0628)